Development and Implementation of Flipbook-Based E-Modules to Enhance the Mastery of Welding Symbols - Syifa, Naeli; Wijaya, M. Burhan Rubai; Basyirun, Basyirun (Journal of Vocational and Career Education, 2024)
The limited mastery of welding symbols among students is a significant challenge in the instruction of basic welding and metal fabrication techniques, which adversely affects the quality of the resulting products. This study aims to develop a flipbook-based e-module to improve the understanding of welding symbols, with its effectiveness assessed through observation, feedback, and testing. The research utilizes the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). An experimental design was employed, comparing an experimental group with a control group, consisting of 72 students from the Welding Engineering and Metal Fabrication program in grade 10th. The findings indicate that the flipbook-based e-module significantly enhanced the mastery of welding symbols. This research highlights the positive impact of integrating technology into education, reinforcing the importance of innovative teaching methods to improve learning outcomes in the field of welding engineering